A Comparative Study of Bone Marrow Aspiration and Bone Marrow Biopsy in Hematological Diseases - Nirajan Mainali; Neha Homagai; Pratap Sagar Tiwari; Arun Giri (Journal of Nobel Medical College, 2015)
Introduction: Bone marrow examination is an important diagnostic tool to evaluate various disorder including both neoplastic and non-neoplastic hematological diseases. The two most important techniques used for the diagnosis are bone marrow aspiration and bone marrow trephine biopsy which are complementary to each other.